ENVIRONMENTAL EFFECTS ON SOMATIC CELL COUNT IN HOLSTEIN COWS AT PARANÁ STATE, BRAZIL - OSTRESKY, André (Scientia Agraria, 2000)
Somatic cell count (SCC) indicates the presence of intrammamary infection in cows. So it may be used for mastitis control, programs of milk quality payment and as a legal parameter of udder health. The objectives of this study were to evaluate the effects of some environmental factors on milk SCC, on somatic cell score (SCS) and on somatic cell logarithm (SCL), as well as to compare SCC and SCS in Holstein cows at Paraná State. A total of 640,937 monthly test-day records was obtained from 40,333 Holstein cows of 378 officially supervised herds by Holstein Association of Paraná State, from January 1994 to December 1998. The Least Square Method was applied, by SAS using PROC GLM. Mean and standard deviation concerning SCC, SCS and SCL were 556,626 ± 835,004 cells/mL, 4.461 ± 1.789 and 8.105 ± 1.789, respectively. Effects such age at calving per lactation calving season (except for SCC), month and year of test-day, as well as days-in-milk, age of milk sample and cows affected the three traits significantly (P<0.01) in this study. The milking frequency effect was not significant (P>0.05) for any of the traits. The statistical summary of SCS has proven to be more meaningful than the results concerning SCC.